A major plant practice at the Food People Incorporated RIS Industrial Complex, Bo. Tabe, Guguinto, Bulacan - Garcia, Dianthe Angelica Canja (2009)
Two hundred and eighty-eight hours of plant practice was conducted at the Food People Incorporated from April to May 2008. The plant practice aimed at exposing the student by letting them experience or to undergo and experience the actual processes in the plant so that they can apply the theories and principles learned in class. Although the little more than one month training is quite short, the student considered it a very rich experience and learning opportunity. Aside from the supplemental knowledge in food technology, the student was able to gather relevant information regarding the plant?s history and background, products, in-line production and processing, quality control and assurance and standard production parameters. This manuscript documents the information collected from the apprenticeship, reports the technical description on the product?s processes and the recommends some solutions to problems encountered in the company in relation to the principles in food technology